Growth Adaptation of Two Indonesian Black Rice Origin NTT Cultivating In Organic Paddy Field, Malang-East Java - Budiman, Budiman; Arisoesiloningsih, Endang; Edi Wibowo, Ratno Bagus (Journal of Tropical Life Science, 2012)
This research is aimed to study the growth adaptation of two Indonesian black rice NTT in origin which is cultivating in organic paddy field in Malang - East Java and its problems during a planting period. A descriptive exploratory research was conducted in two organic rice fields in Kepanjen District, Malang Regency. Those fields were grown with two different varieties of black rice NTT in origin namely, Laka and Woja Laka. Each rice field was recorded periodically. The growth was including the plant height, biomass, density of tiller, panicle and spikes, dry seed weight and the problem correlated to pest and climates limitation. The results showed that Woja Laka and Laka black rice varieties slightly gave a different growth pattern. Laka variety was taller than Woja Laka, i.e. the Laka could reach 200 cm of height, while the Woja Laka was maximum 150 cm of height. However, the density of Woja Laka tiller and its panicle were almost double than the Laka ones. The dry seed weight and spikes number of Woja Laka were much higher than in Laka ones. In terms of organic farming system, Laka rice seemed to be more sensitive towards the strong wind conditions and bird or rat attacks rather than Woja Laka. Both pests attacked on both black rice along growing period, but rat preferred to attack vegetative part, otherwise bird strongly disturbed during generative period. Key words: black rice, growth, Laka, Woja Laka, organic paddy field